Scheduling of air conditioners considering weather forecast error through robust approach - Huang, Xiaowei (2019)
In this report, a robust approach is introduced to schedule the air conditioner energy consumption with consideration of the forecast error. In the power field, many appliances are pre-scheduled based on the weather forecast, however, when some errors occur in the forecast error, the outdoor temperature will deviate from the reference temperature. It may cause the indoor temperature to deviate from the comfort zone as well. Thus, this project aims to use the robust approach to reduce the users’ expense and maintain the comfort indoor temperature. Models and simulation results are presented in the Matlab to demonstrate the effectiveness of the robust approach.